Application of Data Clustering Embedded in Fuzzy Classifier Expert System for Water Quality Recognition - JC Obi; AA Imianvan (Journal of Applied Sciences and Environmental Management)
Water is the energy of life. Its usage and want far out stretch any Earth material (minerals, rocks, soil and water). In most cases the quantity of water obtains from its different sources are not quality enough for human usage due to the presence of contaminants. The application of several criteria for the recognition of water quality (“Might be pure”, “pure” and “Not pure”) is the focal point of this paper. The conventional (traditional) methods for water quality recognition employed by different individuals are expressed using Fuzzy classifier. The proposed expert system eliminates uncertainties and imprecision associated with the recognition of water quality. @JASEM